ANALISIS GERAK LOKOMOTOR SISWA SEKOLAH DASAR KELAS 3 DAN 4 PADA MASA PANDEMI COVID-19 - Yuniar, Sinta Tiara; Nuryadi, Nuryadi; Hambali, Burhan (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
This study aims to provide an overview of the basic locomotor movement skills of elementary school students during the Covid-19 pandemic. The survey was conducted on 154 high school elementary school students aged 8 to 10 years in the Indonesian University of Education environment, the data was observed with instruments developed by Locomotor Movement Skills developed by (Gallahue & Donnelly, 2007), Locomotor Movement Skills related to running (running), jumping forward (horizontal jumping), jumping from a height (jumping from a height) and jumping on one leg (jumping). The researcher concluded that the motor skills stage of high-class elementary school students in school laboratory elementary schools during the pandemic showed students who had early stage (early stage) movement skills, namely 5% for the running test, 15% for the horizontal jump test, 18% for jumping from height test and jump test by 19%. Then for the transition stage (basic stage) there are 55% for the running test, 51% for the horizontal jump test, 57% for the jump test from a height and a jump test of 53%. For students who are already in the mature stage, namely 40% for running, 34% for horizontal jumping, 25% for jumping from a height test and 28% for the hopping test.